2020
DOI: 10.33581/1561-4085-2020-23-2-172-191
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Introduction to Stationary Quantum Chaos in Generic Systems

Abstract: We review the basic aspects of quantum chaos (wave chaos) in mixed-type Hamiltonian systems with divided phase space, where regular regions containing the invariant tori coexist with the chaotic regions. The quantum evolution of classically chaotic bound systems does not possess the sensitive dependence on initial conditions, and thus no chaotic behaviour occurs, as the motion is always almost periodic. However, the study of the stationary solutions of the Schrödinger equation in the quantum phase space (Wigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
(119 reference statements)
2
6
0
Order By: Relevance
“…Our main result is exploring and confirming the Berry-Robnik picture of separating statistically independent regular and chaotic eigenstates and the corresponding energy levels [17] in the semiclassical regime. By means of Poincaré-Husimi (PH) functions we have demonstrated that indeed Principle of Uniform Semiclassical Condensation (PUSC) [25] applies, as the PH functions clearly condense either on invariant tori, or on the chaotic component. In the latter case they can be localized as measured by the entropy localization measure A, but in the strict semiclassical limit become uniformly extended.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our main result is exploring and confirming the Berry-Robnik picture of separating statistically independent regular and chaotic eigenstates and the corresponding energy levels [17] in the semiclassical regime. By means of Poincaré-Husimi (PH) functions we have demonstrated that indeed Principle of Uniform Semiclassical Condensation (PUSC) [25] applies, as the PH functions clearly condense either on invariant tori, or on the chaotic component. In the latter case they can be localized as measured by the entropy localization measure A, but in the strict semiclassical limit become uniformly extended.…”
Section: Discussionmentioning
confidence: 99%
“…The above statements are true provided the Heisenberg time is larger than any classical transport time in the system [7]. If this is not the case, the chaotic eigenstates can be quantum (or dynamically) localized, which implies localized chaotic PH functions to be introduced in the next Sec.…”
Section: The Energy Level Statisticsmentioning
confidence: 90%
See 2 more Smart Citations
“…A general introduction to the subjects in quantum chaos, related to this study, can be found in [3]. Let us also mention the books by Stöckmann [5] and Haake [6] on general quantum chaos and the recent reviews [7,8] on stationary quantum chaos in generic (mixedtype) systems.…”
Section: Introductionmentioning
confidence: 99%